Hybrid manifold smoothing and label propagation technique for Kannada handwritten character recognition - Ramesh, G.; Shreyas, J.; Balaji, J. Manoj; Sharma, Ganesh N.; Gururaj, H. L.; Srinidhi, N. N.; Askar, S. S.; Abouhawwash, Mohamed (Frontiers in Neuroscience, 2024)
Handwritten character recognition is one of the classical problems in the field of image classification. Supervised learning techniques using deep learning models are highly effective in their application to handwritten character recognition. However, they require a large dataset of labeled samples to achieve good accuracies. Recent supervised learning techniques for Kannada Handwritten Character recognition have state-of-the-of-the-art accuracy and perform well over a large range of input variations. In this work, a framework is proposed for the Kannada language that incorporates techniques from semi-supervised learning. The framework uses features extracted from a convolutional neural network backbone and uses regularization to improve the trained features and label propagation to classify previously unseen characters. The episodic learning framework is used to validate the framework. 24 classes are used for pre-training, 12 classes are used for testing and 11 classes are used for validation. Fine-tuning is tested using 1 example per unseen class and 5 examples per unseen class. Through experimentation, the components of the network are implemented in Python using the Pytorch library. It is shown that the accuracy obtained 99.13% makes this framework competitive with the currently available supervised learning counterparts, despite the large reduction in the number of labeled samples available for the novel classes.